Reconsidering our Graduation Efforts: The Economic Impact of Certificates, Associate's, and Bachelor's Degrees. Issue 7 (3rd August 2018) - Tyndorf, Darryl; Martin, Heather
ABSTRACT: United States' education policy efforts have focused on increasing college graduation rates, with an emphasis on bachelor's degrees, with the expectation of greater economic prosperity. Most community college and university degrees differ in time to completion and should not be viewed as having the same short-term, medium-term, and long-term impact on US economic growth. Utilizing the Uzawa–Lucas endogenous growth theory through an econometric model, our research analyzes the impact of total higher education degrees; community college and university graduates; and certificate, associate, and bachelor's degrees on US economic growth. Our findings demonstrate the significant impact of community colleges and community college degrees in the short and medium term on US economic growth compared to university and bachelor's degrees. We conclude with an analysis of the findings and suggestions for future research.